AS “DORES” E AS “DELÍCIAS” DE UMA EQUIPE DE RESIDÊNCIA EM TERRITORIALIZAÇÃO - do Nascimento Moura, Maycom; Gomes Machado, Thamyris Mendes; Caroline Barbosa, Ana; Mesquita de Oliveira, Jordânia Ferreira; de Jesus Bezerra, Samila Cristiany; Castro Gondinho, Bruna Verna; Esteves Santiago, Maria Luci (SANARE - Revista de Políticas Públicas, 2015)
-